The Assessment Of Current 'As Built' Condition And Improvement Of Future Design Of Mosque's Water Closet - Mohamad Nazir, Amni Umirah (2018)
The water closet is an old expression to the toilet. It should include all defecation, urinal, showering and washing facilities. It also refers to water closet cubicle, wash hand basin, shower and all related facilities in the water closet. In Malaysia, there no specific guidelines focusing in mosque water closet facilities and design. A mosque design including its water closet should demonstrate sustainable soundness in design concepts, design requirements, design guidelines, scale, and function. It should provide convenient spaces for all attendees, including the disabled, elderly and children. Ironically, the communal ancillary spaces such as a water closet was frequently ignored. Therefore, this study focuses on mosque water closet and aims at accessing the “as-built” water closet conditions and compared it against Malaysian standards, guidelines, and legislation. Percentage of Compliance and Cleanliness Index were develop based on multicriteria assessment, while the possible causal relationships between water closet cleanliness and condition of microbial contaminants were identified. Based on Percentage Compliance and Cleanliness Index of thirty (31) selected mosques at Pulau Pinang, Melaka, and Perlis, MQS12 reported the highest percentage of compliance (64%) while another thirteen out of thirty-one mosques achieve the acceptable compliance level for water closet design and facilities. Meanwhile, Cleanliness Index (CI), MQS03 recorded the highest, which scored “Good” cleanliness level (83%). Then, the causal relation between Cleanliness Index and microbial contaminants shows that four mosques which recorded higher bacterial contaminants (exceeding the allowable limit of ICOP) has “Not Satisfied” and “Bad” cleanliness level. This may be due to improper design of facilities, which could lead to lower cleanliness index. The new layout which contains three basic facilities (ablution area, water closet cubicle and water closet for disabled) were developed to improve satisfaction level of disabled user with increasing safety and demands of Muslim users. Generally, 50% of mosques has provided minimum compliance on facilities and design, with none scored maximum. The ‘as built’ water closet did not fully comply with Malaysian standards, guidelines and legislation. Cleanliness of water closet could have an effect of microbial growth in the main prayer hall via direct contact of ‘not very clean’ human hand after visiting water closet to the carpet at the main prayer hall. Upgraded design and facilities for water closet being proposed as drawings and modification has shown some positive response from the users hence giving a good ‘signal’ that upcoming water closet should be designed and built with these new features to ensure better conditions in our mosques.